Map of nevi with a surprise - Mazzotta, F; Troccoli, T (European Journal of Pediatric Dermatology, 2006)
This clinical case suggests some considerations as follows: 1- rarity of basal cell carcinomain the pubertal age (3); 2- usefulness of dermoscopyin the differential diagnosis between melanocytic nevus and basal cell carcinoma (2); 3-possibility of performing in case of initial, smallbasal cell carcinoma a topical medical treatment with imiquimod, a new topical drug stimulating the immune system and provided with antineoplastic activity (4), with the aim of preventing probable bad scarring (Fig. 2); 4- necessity of paying attention during the boring nevus maps in children and adolescents.